2017
DOI: 10.1515/fv-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Arrangement of the Subclavian Artery Branches in the Rabbit and European Hare

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…However, the origins and variations of the VA have been observed in the guinea pig, rabbit and hare. [12][13][14] In these studies, the VA entered into the transverse foramen of the C6 in all cases; the authors did not find any malformation of the cervical vertebrae. The study of Chavangvongsanugool et al, 15 observing 58 dogs, showed that the branching patterns of the SA were breed specific.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the origins and variations of the VA have been observed in the guinea pig, rabbit and hare. [12][13][14] In these studies, the VA entered into the transverse foramen of the C6 in all cases; the authors did not find any malformation of the cervical vertebrae. The study of Chavangvongsanugool et al, 15 observing 58 dogs, showed that the branching patterns of the SA were breed specific.…”
Section: Discussionmentioning
confidence: 81%
“…Based on a PubMed search, no studies observing the prevalence of vertebral deformity and anomalous course of the VA in mammals have been published. However, the origins and variations of the VA have been observed in the guinea pig, rabbit and hare 12–14 . In these studies, the VA entered into the transverse foramen of the C6 in all cases; the authors did not find any malformation of the cervical vertebrae.…”
Section: Discussionmentioning
confidence: 85%
“…The variability of the vertebral arteries at the place of origin was studied in laboratory animals and dogs. The course of both vertebral arteries was standard, and they entered into the sixth cervical vertebra and pierced the transverse foramen in all subjects studied [4,5,9,12,13,15]. P o l s et al [15] characterised the branching patterns to the I -scale in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the lateral thoracic artery technique described by Delaere, our aim was to make a flap from the internal thoracic artery. In rabbits, the latter arises from the subclavian artery, runs ventrocaudally parallel to the sternum, and sends perforating branches to the chest wall, constituting the main vascular supply of the mammary glands 19 . The primary aim of adapting this technique is to obtain a bilateral pediculated flap (with both arterial and venous components) through a longitudinal centrothoracic wound, where each one of them will be able to wrap a different construct.…”
Section: Methodsmentioning
confidence: 99%
“…In rabbits, the latter arises from the subclavian artery, runs ventrocaudally parallel to the sternum, and sends perforating branches to the chest wall, constituting the main vascular supply of the mammary glands. 19 The primary aim of adapting this technique is to obtain a bilateral pediculated flap (with both arterial and venous components) through a longitudinal centrothoracic wound, where each one of them will be able to wrap a different construct. The flap is made up of pectoral fascia and a muscular component, which is the cutaneous muscle of the trunk (panniculus carnosus), as in the Delaere technique.…”
Section: Double Tracheal Prelaminationmentioning
confidence: 99%